Nadia and Lili Boulanger - Potter, Caroline 19XX- (Ashgate, 2006)
The author discusses the lives and work of the two Boulanger sisters, both precocious musicians from a very early age. Lili achieved success as a composer before dying at the age of 24 and Nadia, although a successful composer, is best known as a music teacher.
Includes catalogue of Nadia's works, catalogue of Lili's works, and bibliographical references
Keywords: Boulanger, Lili <1893-1918>; Boulanger, Nadia; Boulanger, Nadia -- Biography; Boulanger, Lili -- 1893-1918 -- Biography; Boulanger, Lili -- 1893-1918; Boulanger, Nadia -- 1887-1979; Geschichte 1900-2000; Compositrices - France - Biographies; Musique - France - 20e siècle - Histoire et critique; Professeures de musique - France - Biographies; Musik; Women music teachers -- France -- Biography; Women composers -- France -- Biography; Music -- France -- 20th century -- History and criticism; Frankreich; Biografie; Fiktionale Darstellung